Influence of anaerobic upper-body pre-load exercise on energy metabolism and performance in alpine ski racing - Sieder, M.; Müller, A.; Tschakert, G.; Hofmann, P. (Science and Skiing VII, 2018)
In general, an elevated La concentration before the BJ90 had no negative Influence on jump performance. The results of this study indicate a performance-enhancing capability. The pre-elevated La level inhibits La production and shifts metabolism to a higher oxidative one in a subsequent hlgh-intensity exercise. This concept of the La induction by non-dominant muscle groups may enhance performance in alpine ski racing and other hlgh-intensity sports which Is obviously practiced in top-level World-Cup alpine ski races.